(untitled) (Olhar de Professor, 2023)
With the Covid-19 pandemic, schools around the world paralyzed their face-to-face activities and joined remote activities, reorganizing the physical classroom for the digital environment. As a result, teachers, parents and students had to adapt to this new reality, as well as the activities carried out by the residents. In this way, this work aims to bring reflections on remote teaching in the pandemic from the perspective of the Pedagogical Residency Program in the discipline of science and biology in a public school in the city of Ponta Grossa. Some points observed and experienced during remote teaching were discussed, such as student attendance and participation, based on specialized literature in the area, and also identifying aspects that need to be adjusted. It is necessary to think of different ways to guarantee quality in the teaching-learning process, even though difficulties are present, both on the part of students and teachers.